2021
DOI: 10.1111/cob.12498
|View full text |Cite
|
Sign up to set email alerts
|

Development of a weight bias reduction intervention for third‐year nursing students

Abstract: To explore whether case-based learning will enhance a weight bias reduction (WBR) programme among nursing students to improve their attitudes and beliefs towards persons with obesity. A cluster-randomized controlled trial (CRT) among 13 medicalsurgical clinical practicum groups consisting of six to eight third-year baccalaureate nursing students was conducted to compare a WBR training enhanced by case-based learning (WBR-I, n = 7) with a standard WBR control group (n = 6). All participants completed the Attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…On average, students in this study reported low to medium anti-fat attitudes, low to moderate fat phobia, and modest body appreciation. Our quantitative results did not reveal significant differences between students in the pedagogical intervention compared to those who were not, echoing previous research employing similar content and duration (Elboim-Gabyzon et al, 2020; Oliver et al, 2022; Usta et al, 2021; Werkhoven, 2020; Wijayatunga et al, 2021). However, self-reported BMI was a positive, significant predictor of students’ fear of becoming fat themselves, and this relationship was significant for students in the comparison, but not the intervention, classrooms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On average, students in this study reported low to medium anti-fat attitudes, low to moderate fat phobia, and modest body appreciation. Our quantitative results did not reveal significant differences between students in the pedagogical intervention compared to those who were not, echoing previous research employing similar content and duration (Elboim-Gabyzon et al, 2020; Oliver et al, 2022; Usta et al, 2021; Werkhoven, 2020; Wijayatunga et al, 2021). However, self-reported BMI was a positive, significant predictor of students’ fear of becoming fat themselves, and this relationship was significant for students in the comparison, but not the intervention, classrooms.…”
Section: Discussionsupporting
confidence: 86%
“…Recent interventions focused on reducing weight bias among college students pursuing healthcare-related degrees have yielded mixed results (Oliver et al, 2022; Rukavina et al, 2008; Werkhoven, 2021; Wijayatunga et al, 2019). Some studies have indicated mild improvements in bias reduction, while others have not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 14 studies included, only four used nursing students as the population, and not a single study used NPs. Barra and Singh Hernandez (2018) and Oliver et al (2022) focused on undergraduate nursing education, conducted weight sensitivity education as part of a clinical nursing practicum, and assessed attitudes and beliefs contributing to weight bias over an entire semester and found significant positive changes in students' attitudes after receiving obesity sensitivity education. It is noted that beliefs tend to be most impacted through positive interactions with individuals with lived experiences through evoking empathy.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%